Pembelajaran Holistik – Integratif Anak Usia Dini dengan Pendekatan Cashflow Quadrant di RA Al Muttaqin Tasikmalaya - Hijriyani, Yuli Salis; Machali, Imam (Al-Athfal: Jurnal Pendidikan Anak, 2017)
This article is aimed to figure out the integrative holistic learning process of early childhood which consist of implementation of child health service program, education, child welfare protection, nad child care. The implementation of learning is analyzed by cashflow quadrant approach to see how far the achievement from institute of education for early childhood. This kind of research is qualitative and implemented in RA Al Muttaqin Tasikmalaya. The process of collecting data is using observation, interview and documentation. The data are analyzed using Matthew B Millers Interactive Analyzed Model. The result of this research shows that there is huge support from the organizers of RA Al Muttaqin and aslo some parties who cooperate well toward the instituation. The conclusion of this research is the integrative holistic learning process will run well when the management of financial in the instituation will reach the goal since those factors will bring related to the smoothness of partnering with several parties outside the institution that makes the implementation of services - holistic programs integratif well.